Non-Abelian Hodge Theory and Related Topics - Huang, Pengfei (Symmetry, Integrability and Geometry: Methods and Applications, 2020)
This paper is a survey aimed at the introduction of non-Abelian Hodge theory that gives the correspondence between flat bundles and Higgs bundles. We will also introduce some topics arising from this theory, especially some recent developments on the study of the relevant moduli spaces, together with some interesting open problems.